Primary and Metastatic Cutaneous Melanomas Express ALK Through Alternative Transcriptional Initiation. (June 2016) - Busam, Klaus J.; Vilain, Ricardo E.; Lum, Trina; Busam, Jonathan A.; Hollmann, Travis J.; Saw, Robyn P.M.; Coit, Daniel C.; Scolyer, Richard A.; Wiesner, Thomas
Abstract : A number of common driver mutations have been identified in melanoma, but other genetic or epigenetic aberrations are also likely to play a role in the pathogenesis of melanoma and present potential therapeutic targets. Translocations of the anaplastic lymphoma kinase ( ALK ), for example, have been reported in spitzoid melanocytic neoplasms leading to kinase-fusion proteins that result in immunohistochemically detectable ALK expression. In this study, we sought to determine whether ALK was also expressed in nonspitzoid primary and metastatic cutaneous melanomas. ALK immunohistochemistry was performed on 603 melanomas (303 primary and 300 metastatic tumors) from 600 patients. ALK immunohistochemistry expression was identified in 7 primary and 9 metastatic tumors. In 5 of 7 primary tumors and in 6 of 9 metastatic lesions, the majority of tumor cells were immunoreactive for ALK. In the other 2 primary and 3 metastatic lesions, positive staining was identified in less than half of the tumor cells. ALK positivity was found in the presence or absence of BRAF or NRAS mutations. In contrast to prior observations with ALK-positive Spitz tumors, none of the ALK-positive melanomas harbored a translocation. Instead, the ALK-positive melanomas predominantly expressed the recently described ALK isoform, ALK ATI, which lacks the extracellular and transmembrane domains of wild-type ALK, consists primarily of the intracellular tyrosine kinase domain, and originates from an alternative transcriptional initiation site within the ALK gene. The findings are clinically relevant as patients with metastatic melanoma who have ALK expression may potentially benefit from treatment with ALK kinase inhibitors.